Phytotoxicity assessment study of gold nanocluster on broad bean (Vicia Faba L.) seedling. Issue 1 (31st December 2022) - Hu, Die; Bai, Yumeng; Li, Linlin; Ai, Mingjun; Jin, Jun; Song, Kai; Liu, Duo
ABSTRACT: In this study, we investigated the phytotoxicity of gold nanoclusters (AuNCs) on seed germination capacity, physiological response to stress and uptake, and the transport of gold nanomaterials in broad beans. Although similar findings were observed for AuNCs on broad bean root tip cells between micronucleus assays and traditional phytotoxicity experiments, the former was more sensitive and rapid. At experimental concentrations of 0–200 mg/L, the toxicity performance of broad bean seedlings showed an overall positive correlation with the concentration of AuNCs. AuNCs posed a potential risk to the environment at a concentration of 20 mg/L. Moreover, studies on the uptake and transport of gold nanomaterials showed that the smaller the particles entering the bean, the higher the transport coefficient, while materials not entering the bean were mainly adsorbed on the root surface of the bean seedlings by competition with potassium ions.